Comparative efficacy of ivermectin and Nigella sativa against helminths in Aseel chickens (Gallus gallus domesticus). Issue 5 (28th August 2018) - Angel, C.; Akhter, N.; Arijo, A.; Qureshi, T.A.; Gandahi, J.A.; Qazi, I.H.
Abstract: In this study, we evaluated the in vivo comparative efficacy of ivermectin and Nigella sativa extract against helminths in Aseel chickens, and the effects of helminths on blood parameters before and after treatment in Aseel chickens. Forty naturally infected adult Aseel chickens were randomly divided into four groups ( n = 10 each): group A (ivermectin at 300 μg/kg); group B ( N. sativa extract at 200 mg/kg); group C (ivermectin at 300 μg/kg + N. sativa extract at 200 mg/kg); group D was kept as a positive control to monitor time-related changes. On day 28 post treatment, the mean percentages of faecal egg-count reduction (FECR %) in groups A, B and C were recorded as 93.58, 88.09 and 100.00%, respectively. Further data analysis showed significantly higher efficacy in group C (100 ± 0.00%) than in groups A and B ( P < 0.001). Highly significant ( P < 0.001) improvements in mean percentage values of packed cell volume (PCV %) were recorded in groups A and C on days 14 and 28 post treatment. Meanwhile, the improvements in mean values of haemoglobin (Hb) concentration in groups A, B and C were highly significant ( P < 0.001) when compared to that of group D on day 28 post treatment. The synergistic combination of ivermectin and N. sativa extract possessed greater efficacy than either ivermectin or N. sativa extract used alone. Furthermore, both PCV % and Hb concentration values gradually increased in the treated groups compared to the control group, in which PCV % and Hb concentration gradually decreased throughout the trial.